Recent Advances in High-Entropy Ceramics: Synthesis Methods, Properties, and Emerging Applications - Piyush Chandra Verma; Sunil Kumar Tiwari; Ashish Saurabh; Abhinav Manoj (Ceramics)
High-entropy ceramics (HECs) represent an emerging class of materials composed of at least five different cations or anions in near-equiatomic proportions, garnering significant attention due to their extraordinary functional and structural properties. While multi-component ceramics have played a crucial role for many years, the concept of high-entropy materials was first introduced eighteen years ago with the synthesis of high-entropy alloys, and the first high-entropy nitride films were reported in 2014. These newly developed materials exhibit superior properties over traditional ceramics, such as enhanced thermal stability, hardness, and chemical resistance, making them suitable for a wide range of applications. High-entropy carbides, borides, oxides, oxi-carbides, oxi-borides, and other systems fall within the HEC category, typically occupying unique positions within phase diagrams that lead to novel properties. HECs are particularly well suited for high-temperature coatings, for tribological applications where low thermal conductivity and similar heat coefficients are critical, as well as for energy storage and dielectric uses. Computational tools like CALPHAD streamline the element selection process for designing HECs, while innovative, energy-efficient synthesis methods are being explored for producing dense specimens. This paper provides an in-depth analysis of the current state of the compositional design, the fabrication techniques, and the diverse applications of HECs, emphasizing their transformative potential in various industrial domains.